2019
DOI: 10.1038/s41598-019-51710-y
|View full text |Cite
|
Sign up to set email alerts
|

Relations of non-motor symptoms and dopamine transporter binding in REM sleep behavior disorder

Abstract: The aim of this study was to evaluate associations of motor and non-motor symptoms with dopamine transporter binding in prodromal stage of synucleinopathies. We examined 74 patients with idiopathic REM sleep behavior disorder (RBD), which is a prodromal synucleinopathy, and 39 controls using Movement Disorders Society-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), Montreal Cognitive Assessment, University of Pennsylvania Smell Identification Test (UPSIT), Farnsworth-Munsell 100 hue test, orthostatic tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…44) MDS-UPDRS-III scores (Postuma et al, 2019) and have shown that motor examination signs have a faster progression 1-2 years before phenoconversion (Fereshtehnejad et al, 2019). Moreover, a study stratifying iRBD patients based on the outcome of DAT-SPECT has reported that, in iRBD with or without dopaminergic denervation, MDS-UPDRS-III scores were equal to 10.5 ± 7.5 (indicative of prodromal Parkinson's disease) and 6.0 ± 4.8, respectively, whereas in healthy control subjects the score was equal to 3.2 ± 3.2 (Dusek et al, 2019). Thus, in our iRBD cohort, the relatively high MDS-UPDRS-III score could result from most patients being close to phenoconversion.…”
Section: Discussionmentioning
confidence: 99%
“…44) MDS-UPDRS-III scores (Postuma et al, 2019) and have shown that motor examination signs have a faster progression 1-2 years before phenoconversion (Fereshtehnejad et al, 2019). Moreover, a study stratifying iRBD patients based on the outcome of DAT-SPECT has reported that, in iRBD with or without dopaminergic denervation, MDS-UPDRS-III scores were equal to 10.5 ± 7.5 (indicative of prodromal Parkinson's disease) and 6.0 ± 4.8, respectively, whereas in healthy control subjects the score was equal to 3.2 ± 3.2 (Dusek et al, 2019). Thus, in our iRBD cohort, the relatively high MDS-UPDRS-III score could result from most patients being close to phenoconversion.…”
Section: Discussionmentioning
confidence: 99%
“… 74 Moreover, a study stratifying iRBD patients based on the outcome of DaTScan TM has reported that, iRBD with or without dopaminergic denervation, had MDS-UPDRS-III scores respectively equal to 10.5 ± 7.5 (indicative of prodromal Parkinson’s disease) and 6.0 ± 4.8, whereas healthy control subjects had a score equal to 3.2 ± 3.2. 75 …”
Section: Discussionmentioning
confidence: 99%
“…Hyposmia is recognised as one of the earliest prodromal signs of Parkinson's disease and is present in many patients with isolated RBD. 27,28 In a multicentre study of more than 600 patients with isolated RBD, hyposmia was present in 67%, 1 and back-extrapolation of disease (to estimate the time at which olfaction crossed normal control values) has identified evidence of hyposmia more than 20 years before phenoconversion. 13 The Sniffin' Sticks test (Burghardt, Wedel, Germany), 29 comprising multi-use felt-tip style pens, and the University of Pennsylvania Smell Identification Test (UPSIT), 30 which uses single-use scratch cards, are the most frequently used instruments to assess olfaction, with similar discrimination accuracy.…”
Section: Olfactionmentioning
confidence: 99%